ENGLISH WRITING NEEDS FOR ACADEMIC PURPOSES IN FORMAL HIGHER EDUCATION - Audi Yundayani (Journal of English Language and Literature (JELL), 2017)
The study aimed to get the understanding about the learners’ needs of English writing skill for academic purposes in formal higher education. As a part of English for Specific Purposes (ESP), English for Academic Purposes (EAP) should play an important role in English teaching for non English program, specifically in higher formal education. This is a descriptive research that used observation, questionaire and interview. The data analysis and interpretation indicates that, 1) Learners’ proficiency in English writing for Academic Purposes in formal higher education is a must for use to enhance the learners’ academic performance. It is important for the lecturer to provide the suitable learning material and learning technique based on the requirement; 2) Learners’ English writing skill for academic purposes needs require ability in summarizing, paraphrasing, writing in academic genres like essays, reports and literature reviews, and writing in rhetorical-functional like explaining, defining and drawing conclusion